Maintaining cultures for biotechnology and industry - Hunter-Cevera, Jennie C.; Belt, Angela (Academic Press, 1996)
To retain their usefulness, cultures that manufacture economically valuable products must be uncontaminated, viable, and genetically stable. Maintaining Cultures for Biotechnology and Industry gives practical advice necessary to preserve and maintain cells and microorganisms important to the biotechnology and pharmaceutical industries in ways that ensure they will continue to be able to synthesize those valuable metabolites. This book covers not just those strains currently being used but also those yet to be discovered and engineered. This text is essential for anyone working with cultures who wants to avoid the frustration of losing strains and needs to be able to devise and evaluate new strategies for preservation. Key Features * Written by hands-on experts in their respective fields * Contains helpful tables and protocols for preserving or maintaining cells, cultures and viruses * Discusses means to preserve cells by freezing, lyophilization, drying, cyoprotection, spore storage, continuous propagation and subculturing when absolutely necessary, and others * Gives information needed to test cultures for stable retention of important characteristics * Gives principles needed to devise and evaluate preservation strategies for newly identified and newly engineered cells and organisms * Lists culture sources for each class of organism * Includes information for characterizing and monitoring recombinant organisms, especially important because of their propensity for genetic stability * Discusses the history of the continually evolving field of culture preservation * Examines the importance of genetically stable cultures as it relates to maintaining patent positions.